Consequences of Arsenic Contamination on the Blood Performance and Physiological Status of Anabus testudineus - Islam, Wanaz Nasreen; Rahman, Nasita (Asian Journal of Biological and Life Sciences, 2025)
Background: Arsenic (As) is a naturally occurring element found in several water sources, in the form of Arsenate (As (V)) and Arsenite (As (III)). The widespread use of arsenic-based pesticides coupled with industrial activities and mining operations, has increased the concentration of arsenic in aquatic systems. Chronic exposure of freshwater organisms, such as fish, to low levels of arsenic can result in bioaccumulation which may disrupt the metabolic processes and impair the organ system. Aim: The present work studies the influence of sub-lethal toxicity of sodium arsenite on haematological and histological changes in the liver of a small indigenous fish of Assam, Anabas testudineus. Materials and Methods: Live fishes collected from the fish market after being acclimatized in laboratory conditions, were divided into three groups I, II, and III. Group I was taken as control and Group II and III were exposed to sublethal concentration (15 mg/L) of sodium arsenite for 14 and 28 days respectively. RBC and WBC count was done by Neubauer’s improved haemocytometer using Heyem’s and Turk’s solution as a diluting fluid respectively. Haemoglobin was estimated by Sahli’s method. Blood cell morphology was studied by making blood smear and observed under light microscope. Liver histopathology was studied by Hematoxylin and Eosin (H&E) staining and light microscopy. Results: Arsenic detrimental effects in the blood tissue of the fish increased progressively with increased exposure period. The values of total Erythrocyte Count (RBCs) and haemoglobin concentration decreased with increased duration of exposure but the value of total Leucocyte Count (WBCs), increased contrastingly. The study of the blood cell morphology shows abnormally shaped cells with broken plasma membranes and cytoplasmic blebbing. The liver histology shows degeneration of hepatocytes and sinusoid shrinkage. Conclusion: Arsenic’s toxic effects in aquatic ecosystems are a growing concern, as it impacts the health of individual organisms and can have broader ecological consequences, potentially affecting food webs and biodiversity. Monitoring and managing arsenic levels in water sources and efforts to reduce anthropogenic sources of contamination are critical for safeguarding aquatic life and public health.
Keywords: Arsenic; Fish; Haematology; Histology; Toxic